2006
DOI: 10.5751/es-01667-110128
|View full text |Cite
|
Sign up to set email alerts
|

Trade-offs across Space, Time, and Ecosystem Services

Abstract: Ecosystem service (ES) trade-offs arise from management choices made by humans, which can change the type, magnitude, and relative mix of services provided by ecosystems. Trade-offs occur when the provision of one ES is reduced as a consequence of increased use of another ES. In some cases, a trade-off may be an explicit choice; but in others, trade-offs arise without premeditation or even awareness that they are taking place. Trade-offs in ES can be classified along three axes: spatial scale, temporal scale, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
662
2
26

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,110 publications
(699 citation statements)
references
References 41 publications
9
662
2
26
Order By: Relevance
“…Trade-offs at time scale arises when policy-makers make choices between current and future benefits. Identifying such trade-offs can help policy-makers understand that management decisions should consider the long-term effects of preferring the short-term provision of one ecosystem services at the expense of future use of this same service or other services (Rodríguez et al, 2006). Rodríguez et al (2005) elaborated a broad topic about the temporal trade-offs during decision makings, which revealed that there would be many important trade-offs between current use of nonrenewable resources and their future use.…”
Section: Trade-offs Of Ecosystem Services At Different Scalesmentioning
confidence: 99%
See 3 more Smart Citations
“…Trade-offs at time scale arises when policy-makers make choices between current and future benefits. Identifying such trade-offs can help policy-makers understand that management decisions should consider the long-term effects of preferring the short-term provision of one ecosystem services at the expense of future use of this same service or other services (Rodríguez et al, 2006). Rodríguez et al (2005) elaborated a broad topic about the temporal trade-offs during decision makings, which revealed that there would be many important trade-offs between current use of nonrenewable resources and their future use.…”
Section: Trade-offs Of Ecosystem Services At Different Scalesmentioning
confidence: 99%
“…It is commonly acknowledged that ecosystem services trade-offs occur at different spatial and temporal scale (Rodríguez et al, 2006;Power, 2010) and vary across both space and time (Holland et al, 2011), which increase more uncertainty to be managed. In addition, trade-off analysis from other perspectives are also proposed to be of great significance to land-use management and decision making, such as trade-offs among different stakeholders (Ring et al, 2010) and the reversibility of ecosystem services (Rodríguez et al, 2006).…”
Section: Trade-offs Of Ecosystem Services At Different Scalesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, if the ES concept is to become a fully operational planning tool, it is necessary to move beyond this simplistic perception. Important trade-offs have been recognized between ecosystem management for extracting tangible products (such as food and fibre) versus maintaining intangible services (for example water regulation) (MEA 2005;Rodríguez et al 2006), but less attention has been given to the relationships between intangible ES (Daw et al 2011).…”
Section: Introductionmentioning
confidence: 99%